2012
DOI: 10.7314/apjcp.2012.13.12.5981
|View full text |Cite
|
Sign up to set email alerts
|

MMP1 rs1799750 Single Nucleotide Polymorphism and Lung Cancer Risk: A Meta-analysis

Abstract: Background: Numerous studies have investigated the association of matrix metalloproteinase 1 (MMP1) rs1799750 single nucleotide polymorphism with lung cancer susceptibility, but the findings are inconsistent. Therefore, we performed a meta-analysis to comprehensively evaluate any possible association. Methods: We searched publications from MEDLINE, EMBASE and CNKI databases which assessed links between the MMP1 rs1799750 polymorphism and lung cancer risk. We calculated the pooled odds ratio (OR) and its 95% co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
0
9
0
1
Order By: Relevance
“…On the other hand, we also analyzed the MMP13 -77A/G polymorphism. Compared with several other meta-analysis about MMP polymorphisms and lung cancer risk reported by Guo XT et al 45 , Hu J et al 46 and Wang J et al 47 , we identified more eligible studies, evaluated more SNPs(MMP1-1607 1G/2G, MMP2-1306 C/T, MMP2-735 C/T, MMP9 -1562 C/T and MMP13 -77A/G) and performed analysis by a comprehensive strategy, while they only analyzed single polymorphism and lung cancer risk.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…On the other hand, we also analyzed the MMP13 -77A/G polymorphism. Compared with several other meta-analysis about MMP polymorphisms and lung cancer risk reported by Guo XT et al 45 , Hu J et al 46 and Wang J et al 47 , we identified more eligible studies, evaluated more SNPs(MMP1-1607 1G/2G, MMP2-1306 C/T, MMP2-735 C/T, MMP9 -1562 C/T and MMP13 -77A/G) and performed analysis by a comprehensive strategy, while they only analyzed single polymorphism and lung cancer risk.…”
Section: Discussionmentioning
confidence: 76%
“…MMP polymorphisms and lung cancer risk have been investigated by several meta-analyses 44 45 46 47 . Recently, Hu et al conducted a comprehensive meta-analysis about five MMP polymorphisms and lung cancer susceptibility, and found that the MMP1-1607 1G/2G and MMP2-1306 C/T confer significantly susceptibility to lung cancer, and MMP1-1607’s effect was dependent on ethnicity, consistent with the results of this meta-analysis 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Our research suggests that PLEK2 and SCN7A may be used as potential biological markers for the early diagnosis of NSCLC. [20,21], MMP12 [22], UBE2T [23], ECT2 [24,25], SULF1 [26], HMGB3 [27], and CTHRC1 [28,29]. Besides, we identified PLEK2 and SCN7A as potential biomarkers of NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Hu et al’s results showed that the MMP1 rs1799750 polymorphism is associated with a decreased risk of lung cancer in Asian, but not in Caucasian subjects. 24 Taken together, the relationship between MMP1 rs1799750 polymorphism and cancer risk may be disease-specific and may depend on other factors, such as race, age, habits, etc. There are another two studies that relate to GC and MMP1 , included in Li et al (2013) 25 and Yang et al (2014).…”
Section: Discussionmentioning
confidence: 99%